Three optimal cut-point selection criteria based on sensitivity and specificity with user-defined weights. Issue 3 (1st February 2019) - Li, Dan-Ling; Peng, Jun-Xiang; Duan, Chong-Yang; Deng, Ju-Min
ABSTRACT: Methods : Based on the index S ( S = SENSITIVITY (SEN) × SPECIFICITY (SPE) ), the new weighted product index Sw is defined as Sw = ( SEN ) 2 w × ( SPE ) 2(1- w), where (0≤ w ≤1). The Sw is developed to be a new tool to select the optimal cut point in ROC analysis and be compared with the other two commonly used criteria. Results : Comparing the optimal cut point for the three criteria, the wave range of the optimal cut point for the maximized weighted Youden index criterion is the widest, the weighted closest-to-(0, 1) criterion is the narrowest and the weighted product index Sw criterion lays between the ranges of the two criteria.